Las TIC como herramienta en el proceso de enseñanza-aprendizaje de la Lengua y Literatura - Garzón Salazar, Sofia Lorena (2022)
The investigative work that is put to consideration was developed with the purpose of analyzing the problem that it analyzes: How does the use of ICT as tools influence the teaching-learning process of language and literature in students of the 3rd year of high school? E.G.B. from the Isidro Ayora School of Basic Education?; for which it has been established as a general objective to motivate the use of ICT in educational actions; During the development of each of the work stages, it was important to guide a methodological scheme based on the Mixed approach, the type of research is descriptive correlational; what has contributed significantly to identify as main results that, it has been possible to identify characteristics where only 14% of students manage to understand that the written language is used with different intentions according to the contexts and communicative situations, while 4% demonstrate interest in exploring his classroom and uses ICT to enrich reading and writing activities, defining a clear weakness in the application of strategies with technological support that enhance educational results and objectives, from which the systematization of strategies was feasible. for the application of ICT as tools in the teaching-learning process of Language and Literature, which have a contextualization that adapts to the needs of teachers and students and therefore guarantee that the results are consistent with the required standards by the Ministry of Education for the level.